Removal Of Heavy Metals From Industrial Effluents By Low-Cost Non-Conventional Adsorbents - A. Papandreou (Society for Mining, Metallurgy & Exploration, 2006)
Industrial wastes nowadays constitute one of the most serious threats for the future of our planet. Researchers around the world have very often proposed many kind of solutions in the management problem of industrial effluents. However in most cases suggested solutions are either too expensive to be applied in industrial scale, or they just transfer the problem (e.g. precipitation creates dangerous sludge) and so they create an even greater problem and threat. In the present study the exploitation of valuable hydraulic and adsorption properties of fly ash is studied. Fly ash can easily and cheaply be shaped into stable pellets. After ageing for a sort period of time, these structures can be used as adsorbents for the removal of heavy metals from industrial effluents. Experiments in aqueous solutions have shown excellent adsorption behavior concerning the removal of cadmium, copper, lead, chromium (III) and zinc. The advantage of this technology, except low cost, is that after saturation the pellets can be easily removed from the liquid phase and stabilized in concrete structures without any problem of desorption or leaching. Moreover in these structures a significant amount of cement in the concrete can be replaced by raw fly ash. (Ashcrete as it is called). The utilization of an industrial byproduct as fly ash in the form of pellets as adsorption means and their stabilization with concrete (or ashcrete) combines the useful properties of a solid waste in the treatment of liquid effluents and constitutes a green low cost technology.